Sports-specific adaptations and differentiation of the athlete's heart - Urhausen, A.; Kindermann, W. (Sports Medicine, 1999)
Although the sports-specific adaptations and differentiation of an athlete's heart (AH) were first described 100 years ago, the condition is still an area of active debate. In clinical practice, there is often an obvious lack of basic knowledge concerning the prerequisites and well established extent of the structural and functional characteristics of an AH. Some misunderstandings arise from the somewhat misleading term 'athlete's heart' because not every athlete, even if he or she is training and competing at a very high level, develops an enlarged heart. Such a condition can only be expected after years of quantitative and qualitative demanding aerobic endurance training. Although the correlation with competitive performance of endurance events is rather low in trained athletes, the relationship between heart dimensions and ergometric performance represents an important criterion for differentiation between physiological and pathological cardiac enlargement. The assessment of measures exceeding the usual clinical limits, especially concerning volume-dependent echocardiographic parameters, also requires consideration of the strong influence of anthropometric data. The existence of a concentric left ventricular hypertrophy (LVH) in strength-trained athletes is still a topic of debate in the literature, but is rejected by most recent well-conducted trials. In our review. only bodybuilders using anabolic steroids exhibited a distinctly higher hypertrophic index compared with all other groups of endurance or strength athletes. Current unsolved issues in clinical sports medicine concern the early detection of myocardial complications in athletes exercising during infectious diseases, and the eligibility for competitive sport in cases of borderline LVH.